The Jewish roots of Jesus / Marc Villager. - Villiger, Marc. (Baden, Germany : Visual Productions, 2005)
"If you've ever wondered about life in His times, wanted to know more about Jesus the man and His life, this is the film for you." - -back cover.
The family of Jesus birthplace - -Circumcision - -Hebrew language - -School years - -Feast of the Torah - -Bar Mitzvah - -Training school - -The desert - -Wedding - -Sea of Galilee - -Work - -Feast of the Tabernacles - -The Sabbath - -Rabbi - -Women - -Storytelling - -Exodus - -Death & resurrection.
Keywords: Judaism -- Relations -- Christianity